Mechanism of nodulation and nitrogen fixation in Caucasian clover (Trifolium ambiguum Bieb.) based on transcriptomics and proteomics analyses - Liu, Jiawei; Hao, Xinyan; Guo, Yue; Wang, Mingjiu; Huang, Fan (Frontiers in Genetics, 2025)
IntroductionCaucasian clover (Trifolium ambiguum Bieb.), a perennial legume forage grass, exhibits strong adaptability and resistance to adverse conditions. Owing to its rhizome specificity, it cannot nodulate or fix nitrogen outside of its original location, which limits its promotion and cultivation. The phenomenon of spontaneous nodulation of Caucasian clover was observed for the first time in Inner Mongolia, and investigation of its nodulation and nitrogen fixation mechanisms assists in the subsequent promotion of Caucasian clover cultivation from a theoretical perspective.MethodsIn this study, rhizobia extracted from Caucasian clover were inoculated into the field, and the nodulation part of the root system was investigated during the regreening stage of the second year using transcriptomics and proteomics techniques.Results and DiscussionThe study identified 70,280 differentially expressed genes (DEGs) and 770 differentially expressed proteins (DEPs) in total, among which carbonic anhydrase, cyanate lyase, phenylalanine, caffeate/5-hydroxyferulate 3-O-methyltransferase, caffeoyl CoA 3-O methyltransferase, chalcone synthase, and chalcone isomerase may have been the main factors affecting the nodulation and nitrogen fixation of Caucasian clover. This study theoretically contributes to the future genetic validation and selection of Caucasian clover varieties with a strong ability to nodulate and fix nitrogen.